2021
DOI: 10.1111/dme.14547
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes on COVID‐19 and other infection: Report from the 22nd Hong Kong Diabetes and Cardiovascular Risk Factors—East Meets West Symposium

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has posed enormous challenges to healthcare systems worldwide. The negative impact of COVID-19 is widespread and includes not only people who contracted the disease but also those with chronic morbidities such as diabetes whose care is compromised due to diversion of medical resources. People with diabetes are generally more susceptible to infection as a result of altered immunity. People with diabetes have a worse prognosis from COVID-19 and there is evidence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Additionally, we observed that the odds of COVID-19 were three times higher among patients with type 1 diabetes. Similar results were obtained by other researchers [ 33 , 34 , 35 ]. In a systemic review and a meta-analysis of prevalence and impact of cardiac injury on COVID-19, Fu and colleagues found that the proportions of cardiac injury were 22% amongst 6297 hospitalized patients with COVID-19 [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, we observed that the odds of COVID-19 were three times higher among patients with type 1 diabetes. Similar results were obtained by other researchers [ 33 , 34 , 35 ]. In a systemic review and a meta-analysis of prevalence and impact of cardiac injury on COVID-19, Fu and colleagues found that the proportions of cardiac injury were 22% amongst 6297 hospitalized patients with COVID-19 [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…He had SBS, received parenteral nutrition and had corticoid-induced hyperglycemia. Diabetes and hyperglycemia are also known to predispose to mucormycosis and to severe COVID-19 [ 10 , 11 ]. Elevated glucose levels impair the immune function in several ways, particularly by reducing the innate immune systems’ response towards invading pathogens [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes and hyperglycemia are also known to predispose to mucormycosis and to severe COVID-19 [ 10 , 11 ]. Elevated glucose levels impair the immune function in several ways, particularly by reducing the innate immune systems’ response towards invading pathogens [10] . Both SARS-CoV-2 and Mucorales species enter the endothelial cells through glucose regulated protein 78 (GRP78) [ 8 , 12 ], which is presented on the cell surface during cell stress, including glucose dysregulation and COVID-19 infection [8] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is stated that COVID‐19 susceptibility may increase due to the increase in ACE2 expression in patients with hypertension and using angiotensin receptor blockers (Xu et al, 2020). Due to the suppressive effect of the high blood glucose level on immune function in diabetic patients (Delamaire et al, 1997; Stegenga et al, 2008), and its adverse effects and complications on the circulatory system (Luk et al, 2021), they are at high risk of developing COVID‐19 infection. Since adipose tissue expresses more ACE2 receptors (Jia et al, 2020), it is stated that an increase in BMI poses a risk for severe COVID‐19 (Xu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%